Pandemic Layoffs and the Role of Stay-at-Home Orders - Marianna Kudlyak; Erin L. Wolcott (Institute of Labor Economics (IZA), 2024)
We compile a novel high-frequency, detailed geographic dataset on mass layoffs from U.S. state labor departments. Using recent advances in difference-in-difference estimation with staggered treatment, we find that locally-mandated stay-at-home orders issued March 16–22, 2020 triggered mass layoffs equal to half a percent of the population in just one week. Our findings contribute to explanations for why job loss in 2020 was catastrophic, yet temporary.
Keywords: E32; J63; J64; 330; pandemic; mass layoffs; unemployment; recovery; COVID-19